Особенности распределения давления и его расчета при ползущем течении жидкости в коническом диффузоре - Ульев, Леонид Михайлович (НТУ "ХПИ", 2004)
The problem of creeping liquid flow in a conic channel was solved with the initial condition for pressure which allows to define the cross-section average pressure along the flow. It is exposed that the pressure drop in unlimited channel is finite quantity. The coordinate value with excess which the pressure drop in the channel is changed not more than 1 % was found
Keywords: ламинарные течения; гидромеханика; прямолинейная труба